Accumulation of Polycyclic Aromatic Hydrocarbons in some lichens of Garhwal Himalayas, India. (2nd December 2009) - Shukla, Vertika; Upreti, D.K.; Patel, D.K.; Tripathi, Ranu
Lichens collected from five different sites (11 localities) from Garhwal Himalayas, Uttaranchal, India, were analysed for individual Polycyclic Aromatic Hydrocarbons (PAHs). There was high spatial variability in the total PAH (ΣPAH) concentrations that ranged from 0.683 ppm to 33.72 ppm with an average concentration of 15.04 ± 12.853 (SD). To elucidate sources, six molecular indices (Fluo/Pyr, Phen/Anthr, Naph/Phen, Anthr/(Anthr+Phen), Fluo/(Fluo+Pyr), BaP/BghiP ratios) were used to determine the pyrogenic and petrogenic sources. Garhwal region receives input primarily from vehicular activity and wood combustion; therefore, it can be inferred that the main source of PAH could be pyrolytic.